1988
DOI: 10.1007/bf01218081
|View full text |Cite
|
Sign up to set email alerts
|

Connecting moduli spaces of Calabi-Yau threefolds

Abstract: We demonstrate that many families of Calabi-Yau threefolds consist generically of small resolutions of nodal forms in other families and, in fact, that a large class of families is connected by this relation. Our result resonates with a conjecture of Reid that Calabi-Yau threefolds may have a universal moduli space even though they are of different homotopy types. Such ideas tie quite naturally to alluring prospects of unifying (super)string models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 7 publications
(19 reference statements)
0
64
0
Order By: Relevance
“…Much has been written recently on the role of Calabi-Yau manifolds in supersting theory (see for example [-4, 5, 18, 19, 39, 48]), and many specific examples have been studied in great detail [12,11,13,14,17,36,37]. Recall that a Calabi-Yau manifold is a smooth complex projective threefold with trivial canonical bundle and no global 1-forms or 2-forms -equivalently it is a projective manifold with S U(3) holonomy [2].…”
Section: Introductionmentioning
confidence: 99%
“…Much has been written recently on the role of Calabi-Yau manifolds in supersting theory (see for example [-4, 5, 18, 19, 39, 48]), and many specific examples have been studied in great detail [12,11,13,14,17,36,37]. Recall that a Calabi-Yau manifold is a smooth complex projective threefold with trivial canonical bundle and no global 1-forms or 2-forms -equivalently it is a projective manifold with S U(3) holonomy [2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in physics, the same property provides a mathematical tool to connect topologically distinct compactifications to 4 dimensions of 10-dimensional type II super-string theory vacua. This fact was firstly observed by P. Candelas, A. M. Dale, P. S. Green, T. Hübsch, C. A. Lütken and R. Schimmirgk in [17], [31], [32], [18], [19]. The physical interpretation of a geometric transition connecting two topologically distinct string vacua was given later, in 1995, by A. Strominger [68], at least in the case of a conifold transition i.e.…”
mentioning
confidence: 81%
“…This is the so called Calabi-Yau web conjecture described in many insightful papers starting from 1988 (see [17], [31], [32], [18], [19]). A more precise version of this conjecture will be given later following M. Gross (see 5.3).…”
Section: • Calabi-yau 3-folds Could Be At Least Mathematically Connmentioning
confidence: 99%
See 1 more Smart Citation
“…For physical reasons (such as the compactification of the heterotic string) it became important to study the Hodge theory of Calabi-Yau threefolds (see for example [CHSW, COGP]) and in particular of their Euler numbers (and this carried all the consequences and beautiful predictions nowadays known as mirror symmetry conjectures). The similarity with K3 surfaces already suggested that some kind of finiteness result should hold for Calabi-Yau threefolds (see for example [R, H1, G2]) but the ideas of physics contributed both to clarify what the picture might be for the moduli space of Calabi-Yau threefolds ( [CGH,GH1,GH2,G1]) and, at least from a numerical point of view, what Euler numbers to expect (currently all the known examples satisfy −960 ≤ e(X) ≤ 960 [G1,HS]). …”
Section: Introductionmentioning
confidence: 99%